Teaching Culture to Adult Indonesian Students in English Classrooms: A Mutual Understanding Approach - .J. Hendra Tedjasuksmana (Magister Scientiae, 2013)
Culture is often neglected in FL classrooms while it is important to teach it to the students. In the EFL classrooms in Indonesia, teachers should equip their students not only with the English culture but also other ethnic cultures in Indonesia as Indonesia is a multicultural and multiethnic country. It is English that becomes the bridge for the national unity. This paper describes that students get mutual benefits through learning cultures and it is teachers of English who can play a role of an agent to promote a mutual understanding in the multicultural and multiethnic EFL classroom in Indonesia